If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.60x + 0.05(12 + -1z) = 0.10(-71) 0.60x + (12 * 0.05 + -1z * 0.05) = 0.10(-71) 0.60x + (0.6 + -0.05z) = 0.10(-71) Reorder the terms: 0.6 + 0.60x + -0.05z = 0.10(-71) Multiply 0.10 * -71 0.6 + 0.60x + -0.05z = -7.1 Solving 0.6 + 0.60x + -0.05z = -7.1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + 0.60x + -0.6 + -0.05z = -7.1 + -0.6 Reorder the terms: 0.6 + -0.6 + 0.60x + -0.05z = -7.1 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 0.60x + -0.05z = -7.1 + -0.6 0.60x + -0.05z = -7.1 + -0.6 Combine like terms: -7.1 + -0.6 = -7.7 0.60x + -0.05z = -7.7 Add '0.05z' to each side of the equation. 0.60x + -0.05z + 0.05z = -7.7 + 0.05z Combine like terms: -0.05z + 0.05z = 0.00 0.60x + 0.00 = -7.7 + 0.05z 0.60x = -7.7 + 0.05z Divide each side by '0.60'. x = -12.83333333 + 0.08333333333z Simplifying x = -12.83333333 + 0.08333333333z
| 3y-11=25 | | 8-6d-3+7d=4 | | 3x+5-7-2x=3 | | -2k^2+3k+9=0 | | A+6=-3 | | 5y-3-4y=1 | | 10x+3y=18 | | 3v+7=19 | | 2(a-4)=-3(2a+4) | | 5x-20=9x+10 | | -3b+10=4 | | (x+xy^2)dy+ydx-y^2dx=0 | | 28=5w+3 | | m=52 | | 11g-7=81 | | 7y-28y^3= | | 2x-0.8=-2.5 | | 11m=77 | | -2=-4/2(6)+b | | 12s^2-60s+75= | | 8h-3=5 | | 16x^6-64x^4-9x^2+36=0 | | -5f-6=4 | | 2x+3=.4x | | 5x^2-18x-75=0 | | 2(a-4)=2.3d+3 | | 7x+3=8x-13 | | 2x^2-13=17 | | 5x^3+27x^2+10x=0 | | 990000+xy=19999999 | | 14x-20=9x+10 | | 54r^2-24s^2= |